Confined growth of pyridinic N–Mo₂C sites on MXenes for hydrogen evolution - Wang, Hao (2022)
Developing low-cost and high-performance hydrogen evolution reaction (HER) electrocatalysts is a key research area for scalable hydrogen production from water electrolysis. Here, a hybrid of nitrogen-doped carbon encapsulated Mo₂C nanodots on Ti₃C₂Tx MXene (Mo₂C/Ti₃C₂Tx@NC) is developed through in situ polymerization of dopamine and a Mo precursor on the Ti₃C₂Tx MXene surface. During the annealing treatment, the polydopamine plays multiple roles in forming N-doped carbon, confining MoO₄²⁻ ions into ultrasmall Mo₂C nanodots, and stabilizing the MXene flakes against spontaneous oxidation. The as-synthesized hybrid exhibits excellent HER activity in acidic electrolyte with an overpotential of 53 mV at 10 mA cm(⁻²) and excellent stability over 30 hours. The combination of experiments and simulations demonstrates that pyridinic N-doped carbon coated Mo₂C nanodots serve as the active sites and Ti₃C₂Tx MXene facilitates the charge transfer, synergistically contributing to the superior HER performance.